Analysis of Factors Influencing The Learning Outcomes of Health and Sports Physical Education in Class VII Students of SMP Negeri 3 Huamual - Wa Risa; Emma Rumahlewang; Siti Divinubun (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine what factors influence the learning outcomes of sports and health physical education in class VII students of SMP Negeri 3 Huamual. This research is a quantitative descriptive research. The method used is survey method using a questionnaire as an instrument. This research was conducted at SMP Negeri 3 Huamual with 30 students as samples. The results of the study regarding the factors that influence the learning outcomes of sports and health physical education in class VII students of SMP Negeri 3 Huamual which are in the very high category, namely physiological factors as many as 23 respondents (76.67%) very high category, 7 respondents (23 .33%) high category. Psychological factors as many as 22 respondents (73.34%) very high category, 4 respondents (13.33%) high category, 4 respondents (13.33%) medium category. Social factors as many as 20 respondents (60.67%) very high category, 9 respondents (30%) high category, 1 respondent (3.33%) and non-social factors as many as 17 respondents (56.67%) very high category, 9 respondents (30%) high category, 4 respondents (13.33%) medium category. If we look at the frequency in each category, it can be seen that the dominant psychological factor is in the very high category.